Breathing, One Adult. - Troy, Robin (2012)
Completed 200 pages of a book documenting surviving Hodgkins Lymphoma, a family history describing the experiences both of the author and of her mother.
Keywords: dept.eng; faculty_collection; sabbatical_report

Civil Twilight: Poems - Schilpp, Margot (Carnegie Mellon University Press, 2012)
Mad River Literary Festival Collection
Keywords: 21st century; American poetry; dept.eng; faculty_collection